Optimization of Embung Jinggring for Water Resources Development of the Sadar Watershed, Mojokerto, East Java - Reja Putra Jaya (Journal of the Civil Engineering Forum, 2019)
Embung is a small reservoir which can reserve water exceeds during the rainy season and utilize it on dry season. It is utilized for many purposes, such as providing water for agricultural purposes, fishery, and household needs. Jinggring Weir which is located at Mojokerto Regency, East Java Province is planned to enhance as embung to be able to provide higher water demand services. An appropriate method of water demand optimization study is important for reservoir water management operation to estimate water supply reliability both used for irrigation as well as domestic water. The Mock method was used to analyze water availability, while irrigation, and domestic water requirement, global water balance, simulation of the reservoir operation was analyzed based on Standard Operating Rule (SOR) method. The linear program method is used to determine an appropriate amount of water released to reach the optimum value of water supply reliability. The result of the simulation of target released using SOR method showed that the embung reliability for irrigation and domestic purpose increased from 81.55% to 100% and 80.09% to 100%, respectively.